An Investigation Regarding the Disclosure of Corporate Social Responsibility Information for Listed Companies from Romania - Valentin Dumitru; Iuliana Ionescu; Adriana Calu; Mirela Oancea (Amfiteatru Economic Journal, 2011)
The purpose of this research was to establish the degree of transparency concerning the communication of the information regarding the corporate social responsibility by the Romanian companies listed. The study used as a sample the listed companies in the first part of the Bucharest Stock Exchange. Considering the fact that in Romania there is no mandatory reporting of such information, we examined the extent to which public companies in Romania have, voluntarily, on their sites, such disclosures. As a research framework we used the model proposed by Dahlsrud (2008). According to this model, CSR-type information can be classified into five dimensions: the environmental dimension, social dimension, economic dimension, the ,,stakeholders” dimension and voluntary dimension. After conducting site investigation we made a classification of their degree of transparency (dependent variable). For this variable we tested the association with the type of ownership and activity (independent variables).
Keywords: Q56; 330; Corporate Social Responsibility; CSR dimensions; transparency of CSR; analyses of Romanian companies sites concerning CSR